Ecogeographic study of peanut accessions from the VIR collection - V. D. Bemova; M. Sh. Asfandiyarova; T. V. Yakusheva; V. A. Gavrilova; N. V. Kishlyan (Труды по прикладной ботанике, генетике и селекции)
Background. It has been shown that southern oilseeds, including peanuts, can be successfully grown in the south of the Russian Federation under the conditions of Krasnodar Territory and Astrakhan Province. Currently, only two peanut cultivars are included in the State Register of the Russian Federation: ‘Otradokubansky’ and ‘Astrakhansky 5’. Development of raw material for obtaining new peanut cultivars adaptable to the growing conditions in Krasnodar Territory and Astrakhan Province is a relevant task.Materials and methods. We examined 57 peanut accessions of various origins from the VIR collection. The study of peanut accessions for agronomic characters was carried out in two ecogeographic sites located in Krasnodar Territory and Astrakhan Province. Cv. ‘Otradokubansky’ was used as a reference. ANOVA was applied for statistical data processing.Results and discussion. A wide range of variability in agronomic characters was revealed during the study of peanut accessions. The most stable character was the 1000 seed weight. The share of the genotype the variability of productivity was from 30 to 40%. A great effect of soil and climate factors and the place of cultivation on the ripening of beans was observed. Seed yield depended on the genotype (60–70%) as well as on the temperature factors and the presence of moisture in the soil. The best accessions were selected according to their agronomic characters; they may serve as promising material for breeding. Some accessions are able to produce a good harvest either in Astrakhan Province or Krasnodar Territory, while others can do it regardless of the place of cultivation. This study confirmed the possibility of growing peanuts in Astrakhan Province on medium loamy soils under irrigation, or in Krasnodar Territory on black earth without irrigation.